Особенности развития куколок непарного шелкопряда в различных фототермических условиях - Киреева, И.М. (Вестник зоологии, 1969)
An effect was studied of the temperature (16, 22, 28 and 32°) and illumination (twenty-four-hour illumination, illumination during 17.7 hrs and twenty-four-hour darkness) in various combinations on viability and duration of Porthetria dispar pupa development. It is established that at low temperatures with prolonged illumination period the duration of the pupa development reduces and their viability increases. Under conditions of elevated temperatures the least duration of the development and increased viability of the pupae are observed at 17-hour illumination. The effect of illumination depends on temperature conditions and is most pronounced at a low temperature